Measuring three-flavor neutrinos with FASER$ν$ at the LHC - Tomoko Ariga (SciPost Physics Proceedings, 2025)
FASER$ν$ at the Large Hadron Collider (LHC) is designed to directly detect neutrinos from a collider for the first time and study their cross sections at TeV energies. To date, no such measurements have been made. In 2018, a pilot detector was installed and collected proton-proton collision data of 12.2 fb$^{-1}$ at a center-of-mass energy of 13 TeV. We observed the first neutrino interaction candidates at the LHC, opening a new avenue for studying neutrinos from current and future high-energy colliders. During Run 3 of the LHC from 2022, we will deploy a neutrino detector with a target mass of 1.1 tons. We expect to collect $\sim$2,000 $ν_e$, 6,000 $ν_{μ}$, and 40 $ν_{τ}$ interactions in the detector.